BAHASA MELAYU DI KERAJAAN BUTON (Studi Berdasarkan Naskah Kuno Koleksi Abdul Mulku Zahari di Buton - La Niampe (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Buton is one of Malay Kingdoms which lies in South East Sulawesi. As the time goes by, more and more people from Malay came to Buton. This was due to the strategic position of Buton as trade route in East Nusantara. Besides, this was encouraged by their intention to spread Islam. As a part of Malay Kingdom, the use of Malay language was indispensible. The script collection of ancient texts of Buton Kingdom (Abdul Mulku Zahari’s collection) indicates that Malay Language was taken as one the official languages used in the Kingdom beside Arabic and Wolio languages. From the collection it was found out that Malay (language) scripts were older than Arabic and Wolio scripts (according to its colophon). This language is also used to write scripts about religious teachings, official letters of the Kingdom, adat laws, history, genealogy, literature, traditional medicines, language teachings,and primbon.